El juego en el desarrollo de la creatividad en los niños y las niñas de primer grado de la Unidad Educativa Cerit, en el año lectivo 2021-2022. - Herrera Yugcha, Leslie Anahi (2022)
This research focuses on the problem of not having a clear idea that the game is a tool that supports in numerous ways in the classroom. In this case, we are talking about developing creativity through games and making it known that creativity considers that the child can give solutions to conflicts and children have more extraordinary adaptability to new situations, showing a better attitude to new problems and feeling less frustrated with them. Given all this, the development of creativity through games in children of the Preparatoria Sublevel of the "cerit" Educational Unit has been proposed as an objective. Moreover, the weaknesses and successes in the educational process when developing creative potentialities were examined, considering that this methodology promotes meaningful learning, allowing the children to create their knowledge. This investigation had a quali-quantitative approach, with a projective research type and a feasible and applied project modality; the techniques used were an interview with the authorities, a survey of the teachers and an observation form applied to the students. According to the survey conducted, it was determined that 75% of the teachers implement games as a way of distraction or getting out of the classroom routine, which is why the proposal "I play, I create, and I have fun" was designed. Workshops with fun activities for the development of creativity through games, for which didactic, playful, and easily affordable materials were used to work in the classroom, allowing the improvement of creative skills and abilities in infants and thus increasing the teaching-learning process. The population consisted of 9 infants, 1 authority and 2 kindergarten teachers who are part of the education community. The data collection technique was the interview, the questionnaire as an instrument, and an observation sheet. Based on the results obtained, the aim is to sensitize the different educational agents which interact with children in order to provide attention and facilitate spaces that enable the development of creativity and allow them to express all their imagination and fantasy through play, which is considered a valuable strategy in the creative development of children in the Preparatoria Sublevel.